Modest Aspirations: Day Dreams, Frivolity, and Digital Lives of Public College Girls in Lahore, Pakistan - Khan, Anam (AUC Knowledge Fountain, 2023)
This project was conceived out of a policy announcement in 2016 where the Higher Education Commission Pakistan announced that the two-year colleges were to be phased out and eventually eliminated. In doing so, the notice suggested that they will be replaced by programs modeled around the United States community college and called Associate Degrees. This ongoing development formed the basis of my research as for many gender and class minorities, these programs are the only option for post-secondary education in a country where many do not have the privilege to go to college. I aimed to analyze the kind of education they received during their time, their aspirations, and what they hope to get out of this program. This thesis is divided into three chapters: the first one is called “Daydreams and Aspirations” and it explores a straightforward question: what does the future look like for these girls? Do they have certain aspirations regarding their careers or their home lives? What kinds of lives do they envision for themselves and how do we understand dreams and aspirations from a gendered and classed lens? Following this thread of inquiry, the second chapter is called “Navigating the Mundane: Fun, Frivolity, and Timepass” where I re-examine notions of transgressions, idleness, and the passing of time in college outside of attending classes and studying. Through this perspective, I am making a larger argument about how frivolities like teasing, joking, and doing nothing which are usually dismissed are important points of observation that unravel the complex dynamics of home and personal lives. In doing so, they also act as coping mechanisms and foster communities of support and friendship outside the jurisdiction of the home – which is rare for women who do not have access to public spaces. Finally, the last chapter “Mobile Phones, Digital Lives, and Morality in All-Girls Public Colleges in Lahore, Pakistan” looks at an important terrain in the contemporary moment: digital landscapes. Most women and girls in colleges own a mobile phone or have access to one, yet there is little work has been done on how digital access and mobile phone ownership impact the everyday lives of young, urban, Pakistani girls. By looking at ownership trends and usage of mobile phones, I attempt to understand the complex dynamics of a conservative Pakistani household and young people’s access to the internet. What kind of freedoms or restrictions do these girls have and how do they navigate these terrains? Through these questions, I try to add to my larger argument of how these girls live complex and multi-faceted lives despite living under disciplinary regimes of home and college.